LO89: Describing the evolution of post-concussion symptoms after sports-related mTBI. (May 2020) - Beauchamp, F.; Boucher, V.; Neveu, X.; Ouellet, V.; Archambault, P.; Berthelot, S.; Chauny, J.; de Guise, E.; Émond, M.; Frenette, J.; Lang, E.; Lee, J.; et al.
Abstract : Introduction: Mild traumatic brain injury (mTBI) is a serious public health issue and as much as one third of mTBI patients could be affected by persistent post-concussion symptoms (PPCS) three months after their injury. Even though a significant proportion of all mTBIs are sports-related (SR), little is known on the recovery process of SR mTBI patients and the potential differences between SR mTBI and patients who suffered non-sports-related mTBI. The objective of this study was to describe the evolution of PPCS among patients who sustained a SR mTBI compared to those who sustained non sport-related mTBI. Methods: This Canadian multicenter prospective cohort study included patients aged ≥ 14 who had a documented mTBI that occurred within 24 hours of Emergency Department (ED) visit, with a Glasgow Coma Scale score of 13-15. Patients who were hospitalized following their ED visit or unable to consent were excluded. Clinical and sociodemographic information was collected during the initial ED visit. Three follow-up phone interviews were conducted by a research nurse at 7, 30 and 90 days post-injury to assess symptom evolution using the validated Rivermead Post-concussion Symptoms Questionnaire (RPQ). Adjusted risk ratios (RR) were calculated to demonstrate the impact of the mechanism of injury (sports vs non-sports) on the presence and severity of PPCS. Results: A total of 1676 mTBI patients were included, 358 (21.4%) of which sustained a SR mTBI. At 90 days post-injury, patients who suffered a SR mTBI seemed to be significantly less affected by fatigue (RR: 0.70 (95% CI: 0.50-0.97)) and irritability (RR: 0.60 (95% CI: 0.38-0.94)). However, no difference was observed between the two groups regarding each other symptom evaluated in the RPQ. Moreover, the proportion of patients with three symptoms or more, a score ≥21 on the RPQ and those who did return to their normal activities were also comparable. Conclusion: Although persistent post-concussion symptoms are slightly different depending on the mechanism of trauma, our results show that patients who sustained SR-mTBI could be at lower risk of experiencing some types of symptoms 90 days post-injury, in particular, fatigue and irritability.